2010
DOI: 10.1093/hmg/ddp587
|View full text |Cite
|
Sign up to set email alerts
|

Myosin binding protein C1: a novel gene for autosomal dominant distal arthrogryposis type 1

Abstract: Distal arthrogryposis type I (DA1) is a disorder characterized by congenital contractures of the hands and feet for which few genes have been identified. Here we describe a five-generation family with DA1 segregating as an autosomal dominant disorder with complete penetrance. Genome-wide linkage analysis using Affymetrix GeneChip Mapping 10K data from 12 affected members of this family revealed a multipoint LOD(max) of 3.27 on chromosome 12q. Sequencing of the slow-twitch skeletal muscle myosin binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
137
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 51 publications
1
137
0
Order By: Relevance
“…It has both structural and regulatory roles in muscle function, providing thick filament stability and modulating contractility through interactions with myosin and actin (OMIM 160794). In humans, two mutations in MYBPC1 have been found to cause autosomal dominant distal arthrogryposis type 1, a condition characterized by contractures in the hands and feet 14. Both mutations are SNPs resulting in amino acid exchanges (p.Trp236Arg and p.Tyr856His respectively; Fig 2C).…”
mentioning
confidence: 99%
“…It has both structural and regulatory roles in muscle function, providing thick filament stability and modulating contractility through interactions with myosin and actin (OMIM 160794). In humans, two mutations in MYBPC1 have been found to cause autosomal dominant distal arthrogryposis type 1, a condition characterized by contractures in the hands and feet 14. Both mutations are SNPs resulting in amino acid exchanges (p.Trp236Arg and p.Tyr856His respectively; Fig 2C).…”
mentioning
confidence: 99%
“…An exception to this uncertainty is in the case of distal arthrogryposis, a limb contracture syndrome in which vertical talus is a common feature [15]. Distal arthrogryposis is associated with skeletal muscle abnormalities resulting from sarcomere gene mutations [5,15].…”
Section: Discussionmentioning
confidence: 99%
“…An exception to this uncertainty is in the case of distal arthrogryposis, a limb contracture syndrome in which vertical talus is a common feature [15]. Distal arthrogryposis is associated with skeletal muscle abnormalities resulting from sarcomere gene mutations [5,15]. As the phenotype of distal arthrogryposis is similar to that of isolated vertical talus, we chose to investigate whether similar skeletal muscle abnormalities are present in muscle biopsy specimens of a subset of patients with vertical talus (six of whom had idiopathic vertical talus).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mutations in slow skeletal MyBPC-1 have been linked to skeletal myopathy (Gurnett et al, 2010;Markus et al, 2012), and mRNA injection of mutated MyBPC-1 in zebrafish has been shown to induce structural defects in muscle (Ha et al, 2013). To our knowledge, the fast skeletal MyBPC-2 has not been linked to disease, and no specific transgenic mouse models are available.…”
Section: Mechanical Analysismentioning
confidence: 99%